Violence and its implications for undergraduate nursing education: a literature review - Maffissoni, André Lucas; Sanes, Marina da Silva; Oliveira, Saionara Nunes de; Martini, Jussara Gue; Lino, Monica Motta (Revista Cuidarte, 2020)
Introduction: Violence is a complex social phenomenon, which occurs in various sectors of our contemporary society. Violent acts can be also found in educational processes in different areas of knowledge such as undergraduate nursing education. Objective: To identify how violence occurs over the nursing degree and the possible implications it might have for the training of students. Materials and methods: An integrative review was carried out in the SciELO® virtual library, ERIC®, LILACS®, Web of Science®, MEDLINE®, CINAHL®, Scopus® and Google Academic® databases, from which 21 documents were retrieved for the period between 2014 and 2018. Results: The analysis allowed organizing the results into four categories: characterization of studies and authors; understanding and nature of violence; places where violence occurs and identification of the main perpetrators; and the consequences generated by violence and actions to address this phenomenon. Discussion: Violent acts affect the living conditions of the students involved, impact negatively the development of skills related to interpersonal interaction and generate weaknesses in the training of future nurses. Conclusions: Violence is a constant phenomenon in the context of undergraduate nursing education. It is necessary to promote the strengthening of a culture of peace in this environment. How to cite this article: Maffissoni, André Lucas; Sanes, Marina da Silva; Oliveira, Saionara Nunes; Martini, Jussara Gue; Lino, Monica Motta. Violência e suas implicações na formação em enfermagem: revisão da literatura. Revista Cuidarte. 2020; 11(2): e1064. http://dx.doi.org/10.15649/cuidarte.1064